First demonstration of the neuroepithelial cells and their chemical code in the accessory respiratory organ and the gill of the sharptooth catfish, Clarias gariepinus: A preliminary study. (11th November 2018) - Zaccone, Giacomo; Maina, John; Germanà, Antonino; Montalbano, Giuseppe; Capillo, Gioele; Aragona, Luisa; Kuciel, Michał J.; Lauriano, Eugenia Rita; Icardo, José M.
Abstract: Available studies that have examined O2 sensing in fish have indicated that oxygen‐sensitive neuroepithelial cells (NECs) are O2 sensors in the gills and initiate cardiorespiratory reflexes in aquatic vertebrates. This is the first study describing the occurrence of NECs in accessory respiratory organs in the air‐breathing catfish Clarias gariepinus . Immunocytochemical stainings with specific neuronal markers such as nNOS, VAchT, 5‐HT and TH have been shown to be very useful for location and distribution of these cells in the gill fans and suprabranchial chamber that take origin from the transformation of the gill tissue. But the response of these putative O2 chemoreceptors, their role in the respiratory reflexes and their innervation await investigation.